HIGH TEMPERATURE PROCESSING OF BAUXITE RESIDUE AS A SECONDARY SOURCE OF FERROUS METALS WITH WASTE AND COAL REDUCTANTS - Arisa Mawarni, Falsa
In the aluminium production, bauxite is the primary raw material processed into alumina through the bayer process as the raw material for aluminium production. In bayer process, producing 1 ton of alumina can produce about 1-2 tons of bauxite residue. By 2022, residual bauxite produced from alumina production process reached 175 million tons per year worldwide. Bauxite residue can be considered as a secondary raw material for the recovery of valuable substances such as iron (Fe), aluminium (Al), titanium (Ti), and rare earth elements. On the other hand, there is waste that has not been well managed in Indonesia that can be used as a reductant. In this study, the extraction of iron as the largest component in bauxite residue from PT. Indonesia Chemical Alumina was carried out by pyrometallurgical route using the result of peuyeumisasi sampah (waste reductant) and coal reductants. Series of bauxite residue reduction experiments were conducted to study the effect of temperatures and reductant types on product characteristics in metal and slag. The experiments were carried out by using a horizontal tube furnace (HTF) at a variety of 800-1200°C and reductant type (waste reductant and coal) in a ratio of 1,5 times the stoichiometry requirement based on the fixed carbon basis of the reductant. The reduction process was carried out by flowing argon gas at 2 L/min to create an inert atmosphere in the furnace. The reduction results were mounted, polished, and characterized using Scanning Electron Microscope-Energy- Dispersive X-ray Spectroscopy (SEM-EDS) to determine the microstructure of the sample surface as well as the type of composition of the phases formed in the reduction sample. Based on the experiment results, the reduction of bauxite residue at a temperature range of 800-1200°C with waste reductant showed that the higher the reduction temperature, the higher the iron content in the metal. The highest iron content in the metal phase obtained was 98,84% at 1100°C. At 1200°C, the iron content in the metal decreases due to the increase in the content of other elements in the metal. In the reduction resulted using coal reductant, the highest iron content obtained was 99,58% at 1000°C. At temperatures above 1100°C, the iron content in metal decreases due to a significant increase in the silicon content in metal. The slag phase produced from the reduction of bauxite residue using waste reductant and coal was dominated by Al2O3, SiO2, CaO, Na2O, K2O, TiO, FeO with varying compositions.